2014
DOI: 10.1002/ijc.28688
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime growth and risk of testicular cancer

Abstract: Adult height is associated with testicular cancer risk. We studied to what extent this association is explained by parental height, childhood height and age at puberty. We conducted a case-control study on germ-cell testicular cancer patients diagnosed in [1997][1998][1999][2000][2001][2002][2003][2004][2005][2006][2007][2008] and resident in the Province of Turin. Information was collected using mailed questionnaires in 2008-2011. Specifically, we asked for adult height (in cm), height at age 9 and 13 (compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Genes associated with malignant transformation, proliferation, stemness and pluripotency (KRAS, CCND2, STELLA, NANOG) are located within this region, often amplified in testicular GCT (25,26). Gains of chromosomes 7,8,21, and X are reported in testicular GCT as well (23,25,27). Further genome-wide association studies identified six more loci implicated in testicular GCT, also suggesting the initiation stage in utero [28][29][30].…”
Section: Discussionmentioning
confidence: 96%
“…Genes associated with malignant transformation, proliferation, stemness and pluripotency (KRAS, CCND2, STELLA, NANOG) are located within this region, often amplified in testicular GCT (25,26). Gains of chromosomes 7,8,21, and X are reported in testicular GCT as well (23,25,27). Further genome-wide association studies identified six more loci implicated in testicular GCT, also suggesting the initiation stage in utero [28][29][30].…”
Section: Discussionmentioning
confidence: 96%
“…The EPSAM study is a population‐based case–control study on germ‐cell testicular cancer diagnosed between 1997 and 2008 among residents of the province of Turin, Italy. Full details of our study design have been described elsewhere . The study was approved by the local Ethical Committee and informed consent was obtained from each subject.…”
Section: Methodsmentioning
confidence: 99%
“…Full details of the study design have been described elsewhere (Richiardi et al, 2014). The study was approved by the local Ethical Committee and informed consent was obtained from each subject.…”
Section: Methodsmentioning
confidence: 99%
“…The incidence of testicular cancer has been steadily increasing over the last decades in several populations (Bray et al, 2006) for unknown reasons. There are few established risk factors of testicular cancer: age, geographical area, cryptorchidism, contralateral testicular cancer, height, family history and ethnicity (Richiardi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%